Ordnung - Dieter Schmidtchen; Roland Kirstein (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 1999)
Der Beitrag stellt die Bedeutung von Handlungsbeschränkungen für die Erwartungsstabilisierung und Koordination von Handlungen heraus. An einem einfachen Modell aus der evolutorischen Spieltheorie wird die Bildung von Konventionen und deren Bedeutung für die Reduktion von Transaktionskosten erläutert. – – The paper defines "order" as constraints that are designed or spontaneously evolved to constrain human action sets in order to stabilze expectations, and therefore enhance coordination of interactive behavior. A simple model of evolutionary game theory is used to explain the evolution of conventions and to point out their role in the reduction of transaction costs.
Keywords: D8; C72; 330; Evolutorische Ökonomik; Spontane Ordnung; Transaktionskosten